Inflammatory markers from routine blood tests predict survival in multiple myeloma: a Systematic Review and meta-analysis - Luo, Mengjiao; Qin, Ling; Li, Yujie; Mei, Qianru; Wu, Qiaoping; Feng, Xudong (Frontiers in Immunology, 2025)
BackgroundMultiple myeloma (MM) is an incurable hematologic malignancy marked by abnormal plasma cell proliferation. Inflammatory indices derived from routine blood tests—such as neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), red cell distribution width (RDW), RDW-to-platelet ratio (RPR), and hemoglobin-to-RDW ratio (HRR)—have shown prognostic value across cancers. This meta-analysis aimed to evaluate their prognostic significance in MM.MethodsFollowing PRISMA guidelines, a systematic search of PubMed, Embase, and Web of Science identified eligible studies through January 17, 2025. Pooled hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Sensitivity and subgroup analyses were conducted to assess heterogeneity, and publication bias was evaluated using Egger’s and Begg’s tests.ResultsTwenty-seven studies including 5,009 MM patients were analyzed. Elevated NLR was significantly associated with poor overall survival (OS: HR = 2.06, 95% CI: 1.72–2.47) and progression-free survival (PFS: HR = 1.70, 95% CI: 1.32–2.19), as well as advanced disease stage (OR = 2.85, 95% CI: 1.40–5.80). High RDW and low LMR were similarly linked to worse outcomes (RDW–OS: HR = 1.68; LMR–OS: HR = 0.58). PLR showed no significant association with prognosis. RPR and HRR results were inconsistent due to limited data.ConclusionNLR, LMR, and RDW are promising prognostic biomarkers in MM, with elevated NLR and RDW and decreased LMR indicating poorer outcomes. PLR, RPR, and HRR require further investigation. These routinely accessible indices may aid in clinical risk stratification and therapeutic decision-making.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251105106, identifier CRD420251105106.